ANALYSIS OF WHATSAPP USE IN IMPROVING THE QUALITY OF ADMINISTRATIVE PROCUREMENT DOCUMENT PROCESSING SERVICES AT PT MITRA MANDIRI INFORMATIKA - Amalia Wahyuni; Priatna (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
PT Mitra Mandiri Informatika is a company engaged in the field of Information Technology, specializing in electronic procurement, cybersecurity, IT infrastructure, and software. This study aims to analyze the use of the WhatsApp application in improving the quality of administrative procurement document services at PT Mitra Mandiri Informatika. WhatsApp was chosen due to its ability to facilitate fast, efficient, and accurate communication, both in verbal and written forms. This research uses a qualitative approach with data collection techniques including observation, interviews, and documentation. The results of the study show that the use of WhatsApp provides positive benefits in supporting service processes, particularly in terms of ease of communication, speed of information delivery, cost efficiency, information accuracy, as well as enhancing satisfaction and responsiveness in completing administrative documents. WhatsApp has proven to be an effective and efficient communication tool in improving the quality of procurement administrative services within the company.